Attitudes toward healthy nutrition in Germany — results from an online-representative cross-sectional survey - Hanslian, Etienne; Schiele, Julia Katharina; Jeitler, Michael; Michalsen, Andreas; Wischnewsky, Manfred; Storz, Maximilian Andreas; Brinkhaus, Benno; Ortiz, Miriam; Sigl, Mike R.; Hoffmann, Rasmus; Lehmann, Judith; Koppold, Daniela A.; et al. (Frontiers in Nutrition, 2025)
IntroductionNutrition plays a crucial role in current German public health strategies. While sociodemographic differences in nutrition have been extensively studied, recent data specific to Germany remains limited.MethodsAn online-representative cross-sectional survey was conducted in 2022 among German-speaking adults aged 18–75 using a Computer Assisted Web Interview (CAWI) format. The survey addressed personal eating habits, the importance of nutrition, motivations behind food choices, and openness to dietary changes. Data analysis included both descriptive and inferential statistics, incorporating CHAID decision tree analysis and nonparametric methods for inductive statistical evaluation.ResultsAmong the 4,065 participants, 62.3% regarded healthy nutrition as important, with women, individuals with higher education, and those aged under 26 or over 70 demonstrating greater emphasis on nutrition. CHAID analysis identified education as the most significant predictor of attitudes toward healthy nutrition, followed by sex and income. Participants with a positive attitude toward healthy nutrition reported higher HRQoL scores (EQ-Index = 0.862) compared to neutral or negative attitudes (EQ-Index = 0.835)0.10.5% of participants reported not to eat meat, 28.6% were self-reported flexitarians and 54.1% of participants considered themselves omnivorous. Gender-specific dietary preferences were observed, with plant-based diets being much more popular among females. Participants identified taste preference as the primary factor influencing food choices (77.2%) when asked about the main reasons for their eating habits. Approximately 18% of participants predominantly or exclusively bought organic foods. Interestingly, one third of participants indicated a willingness to adopt a more plant-based diet if recommended by physicians or scientists.ConclusionThis online representative survey revealed significant associations between nutrition and sociodemographic aspects. Understanding this complex interplay might be useful for public health nutrition strategies that promote healthier national eating patterns.